Productive Zakat: Alternatif Solution Empowering Ummah Economy - Suarni Suarni (Proceeding International Seminar of Islamic Studies, 2019)
Zakat is the command of Allah Almighty to His servants to set aside some of the wealth to those who are entitled to receive it. Zakat and prayer have the same position in giving to Allah SWT. The purpose of zakat alms is including realizing the welfare and benefit of the people. To achieve this goal, zakat is distributed not only in consumptive form but also in productive form. The hope is that those who receive zakat can become muzakki who can distribute their zakat to other people. Productive Zakat is one of the most important elements in maintaining the economic balance of the people. The role of zakat is very important in the economic empowerment of the people.